Novel morphologies on flying robots: design for field application - Sampaio, Rafael Coronel Bueno (2015)
Energetic limitations in low scale Unmanned Aerial Vehicles (UAVs) sometimes turns outdoor field applications impractical, which restricts the realization of several tasks that could potentially be improved or benefited from its sounding characteristics. Depending on the mission, Mini Aerial Vehicles (MAVs) energetic resources may be mostly wasted during the round trip from launching base and target point around which a given mission must be accomplished. In this sense, the initial deployment problem becomes prominent, raising new opportunities on how aerial robots may be launched/deployed. This work presents a novel perspective in morphological adaptations for aerial robotics that may potentially minimize initial deployment problem issues. From that perspective, we present three novel morphologies. First refers to a hybrid fixed-wing/quadrotor aiming in-flight launching possibilities. Still looking at in-flight launching, second MAV regards to a new morphology for a quadrotor whose center of gravity is shifted in order to improve passive static stability. Third one relates to a hybrid MAV that combines a watercraft and a quadrotor. The aircraft may navigate on water with low energetic cost through a specially designed structure. It also presents static stability in air and over the ground. We present all details concerning new concepts, development, analysis, design and flight simulation for all three novel platforms. A concise and robust validation of stability control is firstly performed with the ©VICON vision system. Finally, on-the-field evaluation for all three morphologies are extensively carried out, presenting optimistic experimental results of our findings.